Reconceptualization of Sustainability Using the Medical Wheel and Maslow's Pyramid - Ravoaja, Hajaina (Journal of Management Studies and Development, 2024)
This multidisciplinary study revises the concept of sustainability. It aims to provide a more holistic view of this notion. It develops a model that provides a frame of reference for ensuring the sustainability of decisions taken. Comparative analyses of the Sustainable Development Goals (SDGs), a definition of sustainability and its components, the pyramid of needs, and the medical wheel were carried out. Sustainability encompasses the economic, social, ecological, governance, political, technological, legal, and spiritual spheres. The SDGs and this pyramid can be complemented by the need to find meaning in one's life and work through spirituality. This makes it possible to balance the components of sustainability and to consider all the needs. The aspiration to find meaning or purpose in life through spirituality could be added as the 18th SDG. Sustainability is about meeting the physical, mental, emotional, and spiritual needs of current and future generations. Thus, managers will be able to monitor progress in meeting these needs, strike a balance between the components of sustainability, and consider all the needs of their employees. This article provides a missing piece about the needs addressed by the SDGs and those we have categorized into the four strands of the medical wheel that evoke aspects of the human: physical, mental, emotional, and spiritual.